Cost-effectiveness of a community-delivered multicomponent intervention compared with enhanced standard care of obese adolescents: cost-utility analysis alongside a randomised controlled trial (the HELP trial). Issue 2 (15th February 2018) - Panca, Monica; Christie, Deborah; Cole, Tim J; Costa, Silvia; Gregson, John; Holt, Rebecca; Hudson, Lee D; Kessel, Anthony S; Kinra, Sanjay; Mathiot, Anne; Nazareth, Irwin; Wataranan, Jay; et al.
Abstract : Objective: To undertake a cost-utility analysis of a motivational multicomponent lifestyle-modification intervention in a community setting (the Healthy Eating Lifestyle Programme (HELP)) compared with enhanced standard care. Design: Cost-utility analysis alongside a randomised controlled trial. Setting: Community settings in Greater London, England. Participants: 174 young people with obesity aged 12–19 years. Interventions: Intervention participants received 12 one-to-one sessions across 6 months, addressing lifestyle behaviours and focusing on motivation to change and self-esteem rather than weight change, delivered by trained graduate health workers in community settings. Control participants received a single 1-hour one-to-one nurse-delivered session providing didactic weight-management advice. Main outcome measures: Mean costs and quality-adjusted life years (QALYs) per participant over a 1-year period using resource use data and utility values collected during the trial. Incremental cost-effectiveness ratio (ICER) was calculated and non-parametric bootstrapping was conducted to generate a cost-effectiveness acceptability curve (CEAC). Results: Mean intervention costs per participant were £918 for HELP and £68 for enhanced standard care. There were no significant differences between the two groups in mean resource use per participant for any type of healthcare contact. Adjusted costs were significantly higher in the intervention group (mean incremental costs for HELP vs enhanced standard care £1003 (95% CI £837 to £1168)). There were no differences in adjusted QALYs between groups (mean QALYs gained 0.008 (95% CI −0.031 to 0.046)). The ICER of the HELP versus enhanced standard care was £120 630 per QALY gained. The CEAC shows that the probability that HELP was cost-effective relative to the enhanced standard care was 0.002 or 0.046, at a threshold of £20 000 or £30 000 per QALY gained. Conclusions: We did not find evidence that HELP was more effective than a single educational session in improving quality of life in a sample of adolescents with obesity. HELP was associated with higher costs, mainly due to the extra costs of delivering the intervention and therefore is not cost-effective. Trial registration number: ISRCTN99840111 .